ЎЗБЕКИСТОНДА БОЛА ҲУҚУҚЛАРИНИ ҲИМОЯ ҚИЛИШНИНГ ИЛМИЙ-НАЗАРИЙ АСОСЛАРИ - Кадрекова, А.К.; Рахманов, Р.Н. (SCIENCE and SOCIETY, 2021)
We touched upon the scientific and theoretical foundations of protecting the rights of children in our country. At the same time, violation of children's rights is not only a violation of human rights, but also a huge obstacle to the health and development of children, not recognized by society and not well known to the public about maturity.
Keywords: children; children's rights; conventions; constitutions; child welfare